The Influence of Communication, Work Motivation and Work Discipline on Employee Performance - Mawardi, Rimah; Krisnandi, Herry; Digdowiseiso, Kumba (International Journal of Social Service and Research, 2024)
This study aims to determine the effect of communication, work motivation and work discipline on the performance of employees of PT Surgika Alkesido. The sampling method used is Non-Probability Sampling with Purposive sampling technique. This type of research uses quantitative descriptive methods and inferential analysis using primary data in the form of a closed questionnaire to 100 respondents. The data is analyzed using multiple linear regression analysis. From the data that has fulfilled the validity test, reliability test, classical assumption test and model feasibility test, a regression equation is obtained. The regression analysis results in this study indicate a positive and significant effect on customer satisfaction, shown in the coefficient table in the regression equation model. The results of the model feasibility test shown with the significant value shown in the model feasibility table which means that the model in this study is feasible to use based on the significant value obtained. The results of the hypothesis conclusion with the t test obtained a positive and significant value on the variables of communication, work motivation and work discipline on employee performance.